Bloodstream Infections With a Novel Nontuberculous Mycobacterium Involving 52 Outpatient Oncology Clinic Patients―Arkansas, 2018. (16th November 2019) - Labuda, Sarah M; Garner, Kelley; Cima, Michael; Moulton-Meissner, Heather; Laufer Halpin, Alison; Charles-Toney, Nadege; Yu, Peter; Bolton, Erin; Pierce, Reid; Crist, Matthew B; Gomes, Danica; Gable, Paige; et al.
Abstract: Background: In July 2018, the Arkansas Department of Health (ADH) was notified by hospital A of 3 patients with bloodstream infections (BSIs) with a rapidly growing nontuberculous Mycobacterium (NTM) species; on 5 September 2018, 6 additional BSIs were reported. All were among oncology patients at clinic A. We investigated to identify sources and to prevent further infections. Methods: ADH performed an onsite investigation at clinic A on 7 September 2018 and reviewed patient charts, obtained environmental samples, and cultured isolates. The isolates were sequenced (whole genome, 16S, rpoB ) by the Centers for Disease Control and Prevention to determine species identity and relatedness. Results: By 31 December 2018, 52 of 151 (34%) oncology patients with chemotherapy ports accessed at clinic A during 22 March–12 September 2018 had NTM BSIs. Infected patients received significantly more saline flushes than uninfected patients ( P < .001) during the risk period. NTM grew from 6 unused saline flushes compounded by clinic A. The identified species was novel and designated Mycobacterium FVL 201832. Isolates from patients and saline flushes were highly related by whole-genome sequencing, indicating a common source. Clinic A changed to prefilled saline flushes on 12 September as recommended. Conclusions: Mycobacterium FVL 201832 caused BSIs in oncology clinic patients. Laboratory data allowed investigators to rapidly link infections to contaminated saline flushes; cooperation between multiple institutions resulted in timely outbreak resolution. New state policies being considered because of this outbreak include adding extrapulmonary NTM to ADH's reportable disease list and providing more oversight to outpatient oncology clinics. Abstract : A novel nontuberculous Mycobacterium species caused bloodstream infections in 52 cancer patients via contaminated, clinic-compounded saline flushes. Outpatient cancer clinics need support to implement appropriate infection control and prevention measures.